The risk of dementia after coronary artery bypass grafting in relation to age and sex. Issue 6 (4th March 2021) - Giang, Kok Wai; Jeppsson, Anders; Karlsson, Martin; Hansson, Emma C.; Pivodic, Aldina; Skoog, Ingmar; Lindgren, Martin; Nielsen, Susanne J.
Abstract: Introduction: We examined the long‐term risk of dementia after coronary artery bypass grafting (CABG) in relation to age and sex. Methods: All CABG patients in Sweden 1992–2015 (n = 111, 335), and matched controls (n = 222, 396) were included in a population‐based study. Adjusted hazard ratios (aHR) for all‐cause dementia, vascular dementia, and Alzheimer's disease were calculated. Results: There was no difference in the risk for all‐cause dementia between CABG patients and control subjects (aHR 0.98 [95% confidence interval 0.95 to 1.02]). CABG patients <65 years and 65 to 74 years had higher risk (aHR 1.29 [1.17–1.42] and 1.08 [1.02–1.13], respectively), and patients ≥75 years had lower risk (aHR 0.76 [0.71–0.81]). The highest risk was observed in women <65 years (aHR 1.64 [1.31–2.05]). Discussion: Overall, the long‐term risk for all‐cause dementia does not differ between CABG patients and the general population. Younger patients have a higher risk, while older patients have a lower risk, compared to controls.